Autoimmune haemolytic anaemia : a cross sectional study in a Tertiary Haematological Centre - Wahinuddin Sulaiman,; Jasram Singh Sidhu Balwant Singh,; Nur Adlin Syafika Shamzul Hisham,; Nurul Syazwani Zakiah Marhassan,; Siti Aishah Anuar,; Kamini Kirubamoorthy, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Autoimmune haemolytic anaemia (AIHA) is a group of disorders wherein autoantibody causes decompensated acquired haemolysis. There has been no epidemiological study of autoimmune haemolytic anaemia (AIHA) in Malaysia. This study retrospectively analysed the epidemiology of AIHA including Evan’s Syndrome in a Tertiary Haematology Centre in Malaysia. Patients diagnosed with AIHA and Evan’s Syndrome at 18 years old and above between 1 January 1994 to 1 October 2020 at the out-patient Haematology Clinic of Hospital Raja Permaisuri Bainun, Ipoh were selected. Patients’ information was retrieved from the outpatient clinic records. A total of 71 patients were included of which predominantly female. The mean age for both genders were comparable. Ethnic stratification revealed AIHA was higher in Malays followed by Chinese and Indian. Warm AIHA was most prevalent at 40.8%, compared to cold AIHA and Evan’s Syndrome (both 23.9%), and mixed AIHA (11.3%). Primary was more common than secondary AIHA followed by Evan’s Syndrome. Approximately half of the secondary AIHA and secondary Evan’s Syndrome were due to SLE. Overall, 67.6% of patients received corticosteroid only and 28.2% combined with immunosuppressant. Individuals at higher age and females have higher risk of developing AIHA and Evan’s Syndrome. The highest prevalence was seen among the Malay ethnic. Primary warm AIHA is the most common type and majority of Evan’s syndrome are secondary to autoimmune diseases.